A comparison of soil enzyme activities in forest and tea (Camellia sinensis) plantation soil samples - BEZBARUAH, BALAMANI; BORA, TARUN; SALKIA, NEELIMA (The Indian Journal of Agricultural Sciences, 2013)
Soil-enzyme activities with respect to rhodanese, phosphatase, and cellulase of samples obtained from land undertea [Camellia sinellsis (L.) O. Kuntze] cultivation and neighbouring forest land form 3 major tea growing areas of Indiawere evaluated in 1992. The study showed a decreasing trend in cellulase activity in the plantation samples of Assamand Nilgiris compared with the forest samples of that region. Rhodanese activity in the Dooars region was higher inplantation samples but lower in Assam and Nilgiri samples. For phosphatase, the samples from forest of Assam showeda higher activity than the corresponding plantation samples of the region. In all others the phosphatase activity washigher in the plantation samples. Organic carbon values did not appear to have any relationship with cellulase activitydetected in the samples. Grouping the samples on basis of yield oftea did not bring about any relationship between yieldof tea and enzyme activity pertaining to the enzymes evaluated.